(untitled) (Journal of Plant Disease Sciences, 2018)
A field trial was carried out to study the integration effect of soil solarization, bio-agents and fungicides on pre and post-emergence incidence of damping-off disease of chilli for three consecutive years from 2012-13 to 2014-15 during summer season. Soil solarization period of 45 days, soil temperatures at 5cm depth at 8 am, 1 pm and 6 m reached to maximum of 35, 55 and 49.50C under transparent polythene sheet as compared to 31, 46 and 40.50C in non-solarized beds, respectively. It was also observed that due to soil solarization for 45 days during April-May soil temperature increased from 26 to 350C. Due to soil solarization there was rise in morning temperature by 90C over non-solarized. Significant reduction in damping-off of chilli was observed due to soil solarization alone as there was 33.84 per cent damping-off severity in non-solarized plot which reduced to 20.85 per cent when chilli seedlings were grown in the solarized plot. The treatment of soil solarization alone resulted in 34.93 per cent damping-off reduction over check. Among the different fungicides tested maximum disease reduction was recorded due to seed treatment with metalaxyl (50.10 per cent) and captan (44.10 per cent) and were significantly superior over other. Although, seed treatment of Trichoderma harzianum was superior to control, it was less effective compared to fungicides except boric acid. Integration of fungicides with soil solarization showed lower severity of damping off. For effective management of damping-off of chilli, integration of soil solarization with transparent polythene sheet for 45 days in summer followed by seed treatment with metalaxyl @ 3g/kg or captan @ 3g/kg was found most effective.